Proteinuria in early detection of human leptospirosis - K. C., Thresiamma; Biju, Asha; Chaurasia, Reetika; Sritharan, Manjula; Jayaprakash, Chithra; Thomas, Sunil; C. K., Eapen (International Journal of Research in Medical Sciences, 2017)
Background: Leptospirosis is an infectious disease caused by spirochetes bacteria Leptospira spp. and is reported from all over the world. As the clinical signs and symptoms of Leptospirosis often are nonspecific and the disease is early mistaken for other major infectious febrile illness, laboratory test to confirm the clinical diagnosis thus is essential for optimal treatment and patient management. Methods: Serum and urine samples were collected from patients clinically suspected cases of Leptospirosis. Preparations of urine concentrate by precipitation and centrifugation. Results: It was interesting to note that immunoglobulins are present in the urine protein concentrate of patients with Leptospirosis on the day of admission in the hospital, with urine albumin reports either positive or negative. By ELISA test it was noted that antibodies present in urine and serum were of both IgM and IgG class against the Leptospiral antigens from three pathogenic serovars and one non-pathogenicserovars. In the immunospot test which was done and compared with standard ELISA test for serum antibodies using same antigen showed that antibodies present in urine protein concentrate, which was collected on the day of admission when patients come with suspecting symptoms of Leptospirosis. Conclusions: Proteinuria is the most frequent abnormality noted in all patients at some stage of illness. This is the first report on the presence of immunoglobulins in urine samples, which were found to be of IgM and IgG classes. These findings are of significant diagnostic potential as a simple immune-spot test can be done for detecting anti-leptospiral antibodies in urine samples of suspected cases. The present attempt was aimed at developing an immunospot test, a simple and rapid diagnostic test to detect Leptospirosis using urine samples of clinically suspected patients of the infection at the earliest. It was found to be in good correlation with standard ELISA method which is being used to detect serum antibodies in Leptospira infected patients using the same antigen.